POTENSI NANGKA DAN JAMBU BIJI DALAM PENYEMBUHAN DIARE OLEH MASYARAKAT PERUMAHAN SOSA, PADANG LAWAS SUMATERA UTARA - Tania Ermis; Uswatun Hasanah; Chairoel Munawar Rizky; Nuansah Nurifa; Muhammad Fauzi Nasution (Mahesa Research Center, 2021)
This study aims to determine the potential of jackfruit and guava leaves as diarrhea medicine in Lubuk Bunut Village, Huta Raja Tinggi District, Padang Lawas, North Sumatra. This research is explorative in nature, using interviews and questionnaires to the community. Based on the results of interviews and surveys, it was found that two types of plants, namely jackfruit (Artocarpus heterophyllus) and guava (Psidium guajava L.) were used by the community as herbal medicines to cure diarrheal diseases